The relationship between patient deaths in hospital wards and medical students’ emotional distress: evidence from two newly established medical schools in Zimbabwe - Tshababa, Mqemane; Chireshe, Regis; Mutambara, Julia; Patronella Maepa, Mokoena (Frontiers in Psychiatry, 2025)
Patient deaths in hospital wards can have serious emotional and psychological impacts on medical students in the clinical training phase. While the literature reports various levels of distress caused by patient deaths among medical students globally, there is no study on the relationship between patient deaths and medical students’ distress at two newly established medical schools in Zimbabwe. Therefore, this study sought to determine the relationship between patient deaths and medical students’ distress levels. A positivist research philosophy, which utilizes a quantitative approach, was adopted for the study. Gadzella’s (2005) Revised Student-Life Stress Inventory was used to determine the sources and to measure the levels of distress among medical students. A sample of 123 medical students drawn from two newly established medical schools in Zimbabwe participated in the present study. Of these participants, 65 were men (52.8%) and 58 were women (47.2%). The mean age of the participants was 23.4 years. The results indicated significant variations in distress among the different educational levels of medical students at the p < 0.05 level for the five conditions (F = 139.95, p = 0.000). The results of the study revealed that exposure of medical students to dying patients was positively correlated (β = 0.211) with their distress. In addition, the results on exposure to dying patients explained a significant amount of variance in distress (F = 23.519, p = 0.000, R2 = 0.189, R2adjusted = 0.181). A correlation coefficient of R = 0.435 was found, indicating a moderate positive linear relationship between patient deaths and medical students’ distress. The findings of this study highlight that medical students experience emotional distress due to exposure to dying patients. It is recommended that medical students are provided training on emotional resilience and end-of-life care to enable them to handle patient deaths in hospital wards.